Application of the Pale Mahan-Based Tri Hita Karana Learning Model in Grade 3 Theme 3 Subtheme 2 Learning 1 Indonesian Content at Sdn 90 Sipatana (Journal of Pedagogical Inventions and Practices, 2022)
Learning model Tri Hita Karana is a learning model that is oriented to three aspects or concepts of interrelated relationships between God, humans and the environment. In this learning model, it focuses on the environment, which is called Palemahan. The tri hita karana learning model has three stages in the learning process, namely: Stage 1 information/problem orientation, Stage 2 Guiding students in solving problems, Stage 3 Presenting results. The method used is a quantitative research method. From the results of observations, interviews through observation sheets (questionnaire) show that the Tri Hita Karana Learning Based Learning Model is effective in being used in the learning process in elementary schools, because the student responses show that the number of students who answered "Yes" to each question item is more than answer "No". This shows that there is student learning effectiveness, especially in the mindset through group discussions so that students solve problems together in groups.